GE_GERICHTE C/26584/2014 vom 19. Oktober 2016 - GE Cour de justice (2016)
CONDUITE DU PROCÈS; DÉCISION ; DROIT DE GARDE ; DIVORCE ; OBLIGATION D'ENTRETIEN ; ENFANT | CPC.308.1.a; CPC.316.3; CCn.13.c.b; CCn.276.1.2; CCn.276.a.2; CCn.235; CCn.286;